Differential Effects of Problem-Based Learning and Animated Videos on Affective and Cognitive Outcomes in Multi-Grade Elementary Classrooms - Dyaretno Sulistiyowati; Lilik Sri Hariani; Dwi Fauzia Putra (Abjadia : International Journal of Education, 2026)
This study aims to analyze the differential effects of Problem Based Learning and video animation on the affective and cognitive domains of elementary secondary school students. The research approach uses a quantitative method with an explanatory research design. The research population amounted to 53 students, all of whom were sampled through saturated sampling techniques. Affective domain data was collected using a Likert scale questionnaire, while the cognitive domain was measured through learning outcome tests. Data analysis was carried out using the MANOVA test and multiple linear regression with a significance level of 0.05. The results of the study showed that there was a significant simultaneous influence of Problem Based Learning and animated videos on the affective and cognitive domains of students. Partial analysis showed that Problem Based Learning was more dominant in improving cognitive learning outcomes, while animated videos were more powerful in improving students' affective domains. These findings indicate a differential effect between the model and learning media in the context of multiple classes. Proportionate integration of the two approaches is recommended to optimize the quality of learning. This research makes an empirical contribution to the development of evidence-based learning strategies in elementary school dual classes.